(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This paper attempts to investigate the manipulative role of media discourse through examining the coverage of the Syrian crisis in CNN, RT, and the Syrian Satellite Channel (SSC), taking the chemical attack launched by the terrorist groups in Khan al-Assal as an analytical example. The paper attempts to critically assess the way the Syrian Crisis is covered in media reports from a Critical Discourse Analysis (CDA) perspective, focusing on how a particular event is presented by different channels embracing different ideologies. In other words, it is more interested in examining the structure of the news report both schematically and thematically, on the one hand, and the way journalists construct their reports to serve their political agendas, on the other. Consequently, the main objective is to examine how power relations are manifested in the news report, and how media discourse plays a vital role in the construction and reconstruction of power relations and the shaping of the public agenda. Dealing with media discourse as a communicative event, the study will be mainly interested in the linguistic and structural properties of the media report. Aspects of televised news such as camera angle, images, videos, and tone will be ignored, and only the text of the news report will be analyzed. The three news reports in the present case study will be analyzed both thematically and schematically. Using Macrorules, the ultimate objective of this paper is to extract, examine and analyze the discursive tools and strategies each of these channels uses to impose their ideologies and political agendas over the public.